Cooked navy and black bean diets improve biomarkers of colon health and reduce inflammation during colitis. Issue 9 (14th May 2014) - Zhang, Claire; Monk, Jennifer M.; Lu, Jenifer T.; Zarepoor, Leila; Wu, Wendy; Liu, Ronghua; Pauls, K. Peter; Wood, Geoffrey A.; Robinson, Lindsay; Tsao, Rong; Power, Krista A.
<x content-type="archive" xml:space="preserve">Abstract</x> Common beans contain non-digestible fermentable components (SCFA precursors) and phenolic compounds (phenolic acids, flavonoids and anthocyanins) with demonstrated antioxidant and anti-inflammatory potential. The objective of the present study was to assess the in vivo effect of cooked whole-bean flours, with differing phenolic compound levels and profiles, in a mouse model of acute colitis. C57BL/6 mice were fed a 20 % navy bean or black bean flour-containing diet or an isoenergetic basal diet (BD) for 2 weeks before the induction of experimental colitis via 7 d dextran sodium sulphate (DSS, 2 % (w/v) in the drinking-water) exposure. Compared with the BD, both bean diets increased caecal SCFA and faecal phenolic compound concentrations (P< 0·05), which coincided with both beneficial and adverse effects on colonic and systemic inflammation. On the one hand, bean diets reduced mRNA expression of colonic inflammatory cytokines (IL-6, IL-9, IFN-γ and IL-17A) and increased anti-inflammatory IL-10 (P< 0·05), while systemically reduced circulating cytokines (IL-1β, TNFα, IFNγ, and IL-17A, P< 0·05) and DSS-induced oxidative stress. On the other hand, bean diets enhanced DSS-induced colonic damage as indicated by an increased histological injury score and apoptosis (cleaved caspase-3 and FasL mRNA expression) (P< 0·05). In conclusion, bean-containing diets exerted both beneficial and adverse effects during experimental colitis by reducing inflammatory biomarkers both locally and systemically while aggravating colonic mucosal damage. Further research is required to understand the mechanisms through which beans exert their effects on colonic inflammation and the impact on colitis severity in human subjects.